FORWARD MODELING AND DATA INVERSION OF TIME DOMAIN ELECTROMAGNETIC (TDEM) METHOD WITH CENTRAL LOOP CONFIGURATION - Adha Chaerul, Vitasha
The time domain electromagnetic (TDEM) method is one of the active geophysical techniques that provides the subsurface resistivity distribution information by measuring the decay response of the electromagnetic field. Subsurface information from this method is obtained through forward modeling and inversion processes of the observed data, which can only be solved numerically. In forward modeling, numerical expressions are used to transform the magnetic field response from the frequency domain to the time domain using Hankel transformation and Gaver-Stehfest inverse Laplace transformation algorithms, both of which are in the Laplace domain. In this study, the forward modeling results show a high level of accuracy between numerical and analytic calculations in the homogeneous earth case. The maximum error between those two calculations is 0.49%. The validation of the Occam inversion programming code is done by modeling Earth cases with layer variations and disturbances. The Root Mean Square Error (RMSE) values from these models ranges from 0.07 to 0.46. Generally, the forward modeling and Occam inversion formulation used in this study have successfully modeled the subsurface based on the observed data. This is evidenced by the range of RMSE generated, which ranges from 0.09 to 0.57. The modeling results for investigating the saltwater intrusion zone at Santolo Beach show several distinct layers. The first layer is the most resistive among the others, with resistivity ranging from 50 - 350 ohm.m. The second layer has a resistivity of 15 - 50 ohm.m, acting as an aquifer containing fresh water. The subsequent layer is a mixed zone of freshwater and saltwater with resistivity ranging from 5 - 15 ohm.m. Lastly, there is a layer with lowest resistivity ranging from 0.1 - 5 ohm.m at depths below 40 meters, indicating the seawater intrusion zone.